49.5k views
5 votes
5/9 + (1/9 + 4/5)=×


User Logo
by
5.9k points

1 Answer

7 votes

Answer:

22/15

I hope it helps :)

Explanation:


(5)/(9)+\left((1)/(9)+(4)/(5)\right)=x\\x=(5)/(9)+\left((1)/(9)+(4)/(5)\right)\\\mathrm{Remove\:parentheses}:\quad \left(a\right)=a\\x=(5)/(9)+(1)/(9)+(4)/(5)\\\mathrm{Compute\:a\:number\:comprised\:of\:factors\\\:that\:appear\:in\:at\:least\:one\:of\:the\:following:}\\9,\:9,\:5\\=3* \:3*\:5\\\mathrm{Multiply\:the\:numbers:}\:3* \:3* \:5=45\\(5)/(9)=(5* \:5)/(9* \:5)=(25)/(45)\\


(1)/(9)=(1* \:5)/(9* \:5)=(5)/(45)\\\\(4)/(5)=(4* \:9)/(5* \:9)=(36)/(45)\\\\x=(25)/(45)+(5)/(45)+(36)/(45)\\\\\mathrm{Since\:the\:denominators\:are\:equal,\\combine\:the\:fractions}:\\\quad (a)/(c)\pm (b)/(c)=(a\pm \:b)/(c)\\\\x=(25+5+36)/(45)\\\\x=(66)/(45)\\\\x=(22)/(15)

User Pivotal
by
5.6k points